An investigation into the usability of straight light-pipes in Istanbul - (:unkn) unknown (SILA SCIENCE, 2012)
With the impact of global warming, recent years has witnessed a tremendous revival of interest in environmental issues. At the moment, the world's electricity generation mainly depends on the fossil fuels which are eventually going to be run out. On the other hand, fossil fuels have an extremely negative effect on the environment. Therefore, electrical energy savings have become an important factor in the protection of environment. All over the world, lighting of the domestic and commercial buildings as an average consumes about 30% of the electricity produced. One way of the saving electricity in lighting is the utilization of natural daylight. In fact, natural daylight can be a solution for the lighting requirements of the buildings, especially during the daytime. The benefits of using daylight are manifold, such as economical and environmental advantages and the positive effects on human beings. Although there are several methods to use daylight for the illumination purposes, light-pipes are the most simple and versatile of them. In this study, the performance of a light-pipe was investigated in one area, which is a laboratory. The measurements were conducted between February and June. The results of the investigation were presented as the graphs of indoor-outdoor lux versus time. The highest illumination was 449 lux, which was obtained on 12th of May whereas the lowest illumination was 7.51 lux, which was obtained on 26th of February.
Keywords: Daylight; Light-pipe; Energy savings; DAYLIGHT; PERFORMANCES; BUILDINGS; SYSTEMS